IMPACTOS DO PROCESSO DE PRIVATIZAÇÃO NA CULTURA ORGANIZACIONAL DE UMA GRANDE EMPRESA, SOB A ÓTICA DE SEUS COLABORADORES. UM ESTUDO DE CASO SOBRE O BANESPA BANCO DO ESTADO DE SÃO PAULO S.A. - Cruz, Marcelo Alves (2009)
The dynamics that embrace organizations are related to their perpetuation and growth. This growth can be rulled in a organic process, otherwise, with major frequence in a contemporary world, by fusions and acquisitions. One type of acquisiton includes a public agent: the State. This process is knowing by privatization. The approach of this study is the privatization process of a large national company of the brazilian financial market, neither analysing the financial aspects, nor the market, but this work analyses the privatization process of Banco do Estado de São Paulo S.A. Banespa - focusing its organizational culture, by the analysis of the following constructs of organizational culture: socialization of new members, human resources policies, comunication process, organization of working process, historical aspects of company, values and feelings. The first step was a bibliographical research aiming contextualize the fusions and acquisitions processess, which privatization takes part. The research involves either globalization aspects, organizational culture, relations between culture and privatization and inner aspects of brazilian culture. The analysis process demanding two moments required to allow to evaluate the impacts the privatization process takes place in the organization culture: before and after privatization. The particularity of this study is on the informations that alow the analysis: they were obtained with Banespa exemployees, it means, old employees that worked in two moments in the organization: before and after privatization. To identify de cultural elements to be investigated in the study, the interviews were directive. The privatization process by the perception of the ex-employees was also analysed. The research with the old employees identifyed the banespiano figure, one of the most important cultural element, which also was analysed in both moments presented above. Join the bibliographical research, datas of company and the interviews, the author looks for showing the consequences of the privatization process, happened in the end of 2000, to the organizational culture of Banespa.(AU)